Pharmacokinetic and Safety Evaluation of Various Oral Doses of a Novel 1:20 THC:CBD Cannabis Herbal Extract in Dogs - Chicoine, Alan; Illing, Kate; Vuong, Stephanie; Pinto, K. Romany; Alcorn, Jane; Cosford, Kevin (Frontiers in Veterinary Science, 2020)
Objective: To determine the pharmacokinetics (PK) and safety of various oral doses of a Cannabis herbal extract (CHE) containing a 1:20 ratio of THC:CBD in 13 healthy Beagle-cross dogs. Methods: Single-dose PK was assessed after oral administration of CHE at low, medium, or high doses (2, 5, or 10 mg CBD and 0.1, 0.25, or 0.5 mg THC per kg bw, respectively; n=6 per group). Dogs were monitored for adverse events for up to 48 h post-dose. Evaluations of neurological signs, clinical laboratory abnormalities, and other adverse events were performed in two separate study phases; a multiple-dose phase with 12 dogs receiving 5 medium doses (5 mg CBD/kg bw) at 12 h intervals, and a single low-dose (2 mg CBD/kg bw), randomized, blinded, negative controlled study with 13 dogs. Results: Cannabinoids CBD, THC, CBC and metabolites 6-OH-CBD, 7-OH-CBD, 11-OH-THC, and THC-COOH were quantified in plasma. CBD and THC were rapidly absorbed (mean Tmax of 1.9 – 2.3 h) and initially depleted rapidly (mean CBD T1/2 β of 2.3 – 2.6 h). A prolonged elimination phase (mean CBD T1/2 λ of 13.3 – 24.4 h) was observed. CBD and THC concentrations increased in a dose-dependent (non-linear) manner, with disproportionally greater cannabinoid exposure relative to the dose increase. Neurological signs (hyperesthesia or proprioceptive deficits) were noted in 5 of 6 dogs in the high dose group, but only occasionally or rarely in the medium and low dose groups, respectively. Presence and severity of clinical signs correlated with plasma cannabinoid concentrations. Dogs appeared to develop a tolerance to cannabinoid effects after multiple CHE doses, with fewer neurological signs noted after the final (5th) versus first dose. No clinically meaningful changes in blood count or chemistry values occurred after multiple CHE doses. Clinical significance: Dogs tolerated the 1:20 THC:CBD formulation well at low and medium doses, but clinically meaningful neurological signs were observed at high doses. Due to nonproportional increases in plasma cannabinoid concentrations with increasing doses, as well as potential differences in CHE product composition and bioavailability, the possibility of adverse events and dose regimen consistency should be discussed with dog owners.